Association between diastolic blood pressure and cumulative work time - Ricardo Cordeiro; Euclydes Custódio de Lima Filho
Diastolic blood pressure was viewed as a generic indicator of aging, and its association with cumulative work time was studied after controlling for age as a potential confounding factor. The study was conducted among production line workers at a Brazilian tannery in July 1993. The association between diastolic blood pressure and cumulative work time was verified by fitting a second-order linear regression model, where diastolic blood pressure was a function of worker's age and cumulative work time. By fitting the model, one can predict that, in the beginning of working life at the tannery, on average each 1-year period is associated with an increase of about 1.5 mmHg in diastolic blood pressure. The fit obtained highlights one component directly associated with work as part of the rate of pressure increase in the study group. This component is twice as high as that directly associated with age.